2016
DOI: 10.1088/0029-5515/56/3/036024
|View full text |Cite
|
Sign up to set email alerts
|

Non-resonant fishbone-like modes in tokamak plasmas with reversed magnetic shear

Abstract: Energetic ion excited non-resonant fishbone-like modes (FLMs) of m / n  >  1 is investigated for reversed magnetic shear configurations. It is found that the mode can be destabilized by trapped fast ions with a similar excitation mechanism as m / n  =  1 fishbones but with a local interchange-like mode structure, which is in agreement with previous experiments (Toi et al 1999 Nucl. Fusion 39 1929). The dispersion relation of the mode is derived for m / n  >  1. The radial mode structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…the rotation frequency of the m/n = 2/1 magnetic islands is locked gradually. The radial magnetic component δB r and spatial phase angle φ 0 for the LMs are measured by the saddle loops, as shown in figure 2(e), which can be expressed as in [32]: δB r = B r0 • cos(nφ − φ 0 ), where eight magnetic loops are located in the lower field side (LFS) of the equatorial plane along the toroidal direction φ. The n = 1 magnetic island is locked by the tungsten protector limiter (−0.4π φ Lim −0.3π) for t 3.66 s, and the 3D intrinsic error fields are formed accordingly.…”
Section: Mode Lockingmentioning
confidence: 99%
“…the rotation frequency of the m/n = 2/1 magnetic islands is locked gradually. The radial magnetic component δB r and spatial phase angle φ 0 for the LMs are measured by the saddle loops, as shown in figure 2(e), which can be expressed as in [32]: δB r = B r0 • cos(nφ − φ 0 ), where eight magnetic loops are located in the lower field side (LFS) of the equatorial plane along the toroidal direction φ. The n = 1 magnetic island is locked by the tungsten protector limiter (−0.4π φ Lim −0.3π) for t 3.66 s, and the 3D intrinsic error fields are formed accordingly.…”
Section: Mode Lockingmentioning
confidence: 99%
“…This is the case for the ITER scenario considered in the present work. We note that this is different from the off-axis FB [25][26][27] (also called FB-like mode) where the dominant component has the poloidal mode number larger than 1.…”
Section: Introductionmentioning
confidence: 59%
“…In these tokamak devices, the modes can lead to large fast ion transport and the formation of internal transport barrier, which result in broadening the distribution of the fast ions. Based on these relative experiment results, the physical mechanisms of the non-resonant EPM have been also numerically investigated in previous works [31][32][33]. For the equilibrium and the stability of the non-resonant EPMs, Wang et al found the experimental level of plasma rotation hardly has any impact on them.…”
Section: Introductionmentioning
confidence: 97%